2019
DOI: 10.1111/jfpe.13019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of transport properties and mechanistic modeling of the coupled salt and water transport during osmotic dehydration of salmon induced by dry salting

Abstract: A mechanistic forward osmosis model based on nonideal principles and the continuity equation was adapted to the dry salting of salmon. The novelty of this model is that the water loss is coupled to the salt uptake by means of the activity gradient. Consequently, besides the primarily desired predictive purposes, the model also explains why the ion uptake triggers the osmotic dehydration. The determination of the model parameters, as well as the validation of the model was carried out by comparing the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition to sensory analysis and microbiological assessment, a wide range of physicochemical measurements has been widely tested for evaluating quality changes in meat and fish and derivative products resulting from the application of traditional processes. These include, but are not limited to, chemical composition, pH, water-holding capacity, k value, volatile compounds, lipid and protein oxidation [3,44,53,[56][57][58][59]. However, most of these techniques and approaches share general limitations, including the destructiveness of the sample and the time required for the analysis, in addition to specific challenges that are applicable to each of these methods.…”
Section: Classical Methods Used To Evaluate Quality Changesmentioning
confidence: 99%
“…In addition to sensory analysis and microbiological assessment, a wide range of physicochemical measurements has been widely tested for evaluating quality changes in meat and fish and derivative products resulting from the application of traditional processes. These include, but are not limited to, chemical composition, pH, water-holding capacity, k value, volatile compounds, lipid and protein oxidation [3,44,53,[56][57][58][59]. However, most of these techniques and approaches share general limitations, including the destructiveness of the sample and the time required for the analysis, in addition to specific challenges that are applicable to each of these methods.…”
Section: Classical Methods Used To Evaluate Quality Changesmentioning
confidence: 99%
“…However, there were significative differences (p<0.05) for ash content between 10 °C and 15 °C at 12 h; 30 °C at 24 h and 72 h, respectively. This little variation could be related to the salt gain during the dry salting process, as previously stated, the salt diffusion can be affected by the stage of the salting [32], nature and composition of the meat tissue [33,34,35]. The turkey neck after 96 h of salting showed 13.45% of fixed mineral residue (ash) for all treatments, where the Brazilian Legislation establishes a maximum limit of 23% for charqui [47].…”
Section: Physicochemical Changes During the Dry Salting Kineticsmentioning
confidence: 77%
“…The Turkey neck meat structure is abundant both in muscle and connective tissue, heterogeneously distributed through the meat. Martínez-Lopez, Bertelsen and Jessen (2019) [34] described differences in salt diffusion between the skin and the meat during dry salting of salmon and observed that the limit between the muscle and the skin is permeable until salt to reach the saturation point and the flux is interrupted and until the system arrives at stationary state. Thus, in this work could be occurred the similar effect described by these authors, which suggested that salt intake at different rates both the skin and the muscle interfaces.…”
Section: Water Loss and Salt Gain During Dry Salting Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate validations must be done to check the accuracy of the model. Numerical models have been proposed based on the first principles of heat and mass transfer that studies the salting kinetics of salmon to predict state variables as a function of time and space (Martínez-López et al, 2019;Wang et al, 1998Wang et al, , 2000. Empirical models, such as Peleg's or Zugarramurdi and Lupin's models, can also be applied to predict salt and water concentrations based on mathematical equations obtained from experimental data.…”
Section: Modelling Water Holding Propertiesmentioning
confidence: 99%